Wine purchase and consumption in Portugal - an exploratory analysis of young adults' motives/attitudes and purchase attributes - Duarte, Filomena (2010)
This study, exploratory in nature, examines how motives/attitudes, purchase and consumption behaviour, as well as extrinsic attributes for wine choice, of Portuguese young adult’s (aged less than 35 years), differ from other age segments. With this aim an online survey was used, resulting in 1160 usable responses. Using factor and cluster analysis, based on motivation/attitudes towards wine consumption, four segments were obtained: “Enthusiast”, “Regular”, “Infrequent” and “Convivial” wine drinkers. Results show that despite some similarities, young adults (more represent in the two last clusters), particularly those under 24 years, show signifi cant differences concerning the analysed factors.